1991
DOI: 10.3109/03008209109029157
|View full text |Cite
|
Sign up to set email alerts
|

Vascular collagen fibril morphology in type IV ehlers-Danlos syndrome

Abstract: Morphometric analysis of transmission electron micrographs of blood vessel, skin and dura mater collagen fibers were performed on postmortem tissues taken from 28-year-old female with Ehlers-Danlos type IV syndrome (EDS IV). Vascular tissue from this patient was compared to 5 age- and sex-matched controls (age range 26-28 years). Our study revealed significant variation in collagen fibril diameter in the walls of almost all the vessels studied. In general, the EDS IV tissue showed a net decrease in average col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The vascular pathology in this case was most apparent in the ruptured bowel, but was also seen at the liver hilum and elsewhere in the abdomen and retroperitoneum: blood vessels in these areas had walls that varied in thickness and had discontinuous and frayed elastic tissue fibers. Thin vascular collagen fibrils in affected patients [17] probably account for some of the variation in their vessel wall thickness. Vessels from the bowel of other patients with EDS type IV have fibrotic [18] and discontinuous [19] muscle layers.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular pathology in this case was most apparent in the ruptured bowel, but was also seen at the liver hilum and elsewhere in the abdomen and retroperitoneum: blood vessels in these areas had walls that varied in thickness and had discontinuous and frayed elastic tissue fibers. Thin vascular collagen fibrils in affected patients [17] probably account for some of the variation in their vessel wall thickness. Vessels from the bowel of other patients with EDS type IV have fibrotic [18] and discontinuous [19] muscle layers.…”
Section: Discussionmentioning
confidence: 99%
“…Case studies have indicated that arteries in individuals with EDS IV may have thin walls, poorly organized collagen layers, or reduced distensibility [2][3][4]. Such morphological features may be detectable by non-invasive imaging and offer a target for assessing prognosis or evaluating potential treatments.…”
mentioning
confidence: 99%
“…4 Arteries of the thorax and abdomen are the most commonly involved, but extremity and head/neck arteries may also be affected. 4,6 More specifically, arterial manifestations have been described in the aorta, 7 the carotid artery, 4,5,8 intracranial arteries, 6,9,10 the cervical artery, 8 the splenic artery, 11,12 the renal artery, 11,13 the iliac artery, 14 the celiac artery, the hepatic artery, the superior mesenteric artery, and the pancreaticoduodenal artery. 11 Uterine rupture in association with EDS type IV typically occurs in late pregnancy.…”
Section: Prahlow and Wagnermentioning
confidence: 98%
“…[1][2][3][4] Type III collagen is found in blood vessels, skin, and hollow viscera, and these locations tend to be affected in EDS type IV. 3,5 Joint hypermobility and hyperextensibility of the skin are relatively unusual in the vascular form of EDS. 4,6 The clinical diagnosis of EDS type IV is based on 4 clinical criteria: easy bruising, thin skin with visible veins, characteristic facial features, and a propensity for arterial, uterine, or intestinal rupture.…”
Section: Prahlow and Wagnermentioning
confidence: 99%
See 1 more Smart Citation